(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the linguocultural specificity of color terms in the Uzbek language, focusing on their semantic, symbolic, and cultural functions. Color terminology is analyzed not merely as a means of visual categorization but as an important linguocultural code reflecting national mentality, historical experience, and collective values. The study is based on a qualitative linguocultural methodology that combines descriptive, semantic, contextual, and comparative analysis. The study confirms that color terms in Uzbek play a significant role in shaping linguistic worldview and cultural conceptualization. The results contribute to linguocultural research by systematizing the cultural semantics of Uzbek color terminology and highlighting the interaction between language, culture, and cognition.